ΔNp63α expression induces loss of cell adhesion in triple-negative breast cancer cells - Nekulova, Marta (BMC Cancer, 2016)
BACKGROUND: p63, a member of the p53 protein family, plays key roles in epithelial development and carcinogenesis. In breast cancer, p63 expression has been found predominantly in basal-A (epithelial-type) triple-negative breast carcinomas (TNBC). To investigate the functional role of p63 in basal-A TNBC, we created MDA-MB-468 cell lines with inducible expression of the two major N-terminal p63 isoforms, TAp63α and ∆Np63α. RESULTS: TAp63α did not have significant effect on gene expression profile and cell phenotype, whilst the main effect of ΔNp63α was reduction of cell adhesion. Gene expression profiling revealed genes involved in cell adhesion and migration whose expression relies on overexpression of ΔNp63α. Reduced cell adhesion also led to decreased cell proliferation in vitro and in vivo. Similar data were obtained in another basal-A cell line, BT-20, but not in BT-549 basal-B (mesenchymal-like) TNBC cells. CONCLUSIONS: In basal-A TNBC cells, ∆Np63α has much stronger effects on gene expression than TAp63α. Although p63 is mentioned mostly in connection with breast cell differentiation and stem cell regulation, we showed that a major effect of p63 is regulation of cell adhesion, a process important in metastasis and invasion of tumour cells. That this effect is not seen in mesenchymal-type TNBC cells suggests lineage-dependent functions, mirroring the expression of ∆Np63α in primary human breast cancers. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12885-016-2808-x) contains supplementary material, which is available to authorized users.